Treatment of Herpes simplex encephalitis with the helicase-primase inhibitor pritelivir in an immunocompromised patient - Catherina Lueck; Christina Rautenberg; Alexander Birkmann; Susanne Bonsmann; Alessandra Marini; Melanie Sumner; Thomas Schroeder; Sebastian Voigt (npj Antimicrobials and Resistance, 2026)
Abstract Pritelivir, a novel helicase-primase inhibitor, has successfully completed a global Phase 3 trial for refractory herpes simplex virus (HSV) infections in immunocompromised patients. This case report is the first clinical use of pritelivir in Herpes simplex encephalitis (HSE). An allogeneic hematopoietic cell transplant recipient developed HSE and was treated with acyclovir. After 1.5 months, while still on valacyclovir prophylaxis, HSE relapsed, confirmed by Magnetic Resonance Imaging (MRI) and HSV1 DNA detection in cerebrospinal fluid (CSF). Following transient response to acyclovir and foscarnet, combined pritelivir/acyclovir treatment was initiated in this comatose patient with cerebral edema and necrosis. Clinical improvement occurred with increased alertness and motor activity, enabling discharge to rehabilitation. MRI showed no further progression, and CSF HSV DNA load became undetectable. No relevant adverse effects were observed. Pritelivir plasma and CSF concentrations exceeded the 50% effective concentration for HSV1. This case highlights the potential of pritelivir for treating HSE.